A baseline epidemiological survey for malaria and schistosomiasis reveals an alarming burden in primary schools despite ongoing control in Chikwawa District, southern Malawi - Blessings Chiepa; Rex Mbewe; Michelle C. Stanton; Blessings Kapumba; Eggrey Kambewa; Lucy Kaunga; John Chiphwanya; Themba Mzilahowa; Christopher M. Jones; J. Russell Stothard (Current Research in Parasitology and Vector-Borne Diseases, 2024)
Our study rationale was to establish contemporary epidemiological data on malaria and schistosomiasis among school-going children in Chikwawa District before future environmental changes associated with the Shire Valley Transformation Programme occurred. Our cross-sectional surveys tested 1134 children from 21 government-owned primary schools (approximately 50 children per school); rapid diagnostic tests for malaria (Humasis Pf/PAN) and intestinal schistosomiasis (urine-Circulating Cathodic Antigen) were used, with urine reagents strips and egg-filtration with microscopy for urogenital schistosomiasis. All infected children were treated with an appropriate dose of Lonart® (for malaria) and/or Cesol® (for schistosomiasis). Across 21 schools the overall prevalence was 9.7% (95% CI: 8.8–10.6%) for malaria, 1.9% (95% CI: 1.4–2.3%) for intestinal schistosomiasis, and 35.0% (95% CI: 33.6–36.5%) for egg-patent urogenital schistosomiasis. The prevalence of co-infection of malaria with urogenital schistosomiasis was 5.5% (95% CI: 4.8–6.2%). In a third of the schools, the prevalence of malaria and urogenital schistosomiasis was above national averages of 10.5% and 40–50%, respectively, with two schools having maxima of 36.8% and 84.5%, respectively. Set against a background of ongoing control, our study has revealed an alarming burden of malaria and schistosomiasis in southern Malawi. These findings call for an immediate mitigating response that significantly bolsters current control interventions to better safeguard children's future health.